Smart city applications: Transportation in Istanbul - AYTEKİN, ÇİĞDEM (Peter Lang, 2021)
#e exponential growth in urbanization around the globe has resulted in a population density in narrow residential areas. It brings along many problems and has a negative impact on sustainable city life. #e high tra$c congestion is one of the leading problems of city life in the most crowded city of Turkey, Istanbul. #e research aims to provide information and knowledge regarding the policy formulation process for transportation in İstanbul. It also includes the discussion of the backgrounds of the “smart city” concept, and the subject in question, based on technological theoretical foundations such as “Internet of #ings” and “Internet of Everything,” and aims to examine the factors to determine criteria to be a smart city citizen. Although these factors seem similar to each other, they involve di!erent elements as well. #is situation leads to the di!erences between the indexes developed for a smart city. We will evaluate the seven smartest cities in the world (London, Singapore, New York, Chicago, Amsterdam, Barcelona, and Paris), and examine the smart city applications of these cities to "nd a solution for the transportation problems by assembling the seven indexes that Ho!man refers to. #e conclusion includes the adaptable applications we will examine, to deal with the transportation problem of Istanbul.
Keywords: smart cities; smart city index; transportation services; internet of things; internet of everything